2021
DOI: 10.1002/widm.1431
|View full text |Cite
|
Sign up to set email alerts
|

Detecting communities using social network analysis in online learning environments: Systematic literature review

Abstract: Uncovering community structure has made a significant advancement in explaining, analyzing, and forecasting behaviors and dynamics of networks related to different fields in sociology, criminology, biology, medicine, communication, economics, and academia. Detecting and clustering communities is a powerful step toward identifying the structural properties and the behavioral patterns in social networks. Recently, online learning has been progressively adopted by a lot of educational practices which raise many q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 103 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…The research focuses on the single-ethnic research at the meso-level and the research on colleges and universities [11]. As far as the relevant research results have been found so far, few scholars have discussed the relevant issues of "forging the consciousness of the Chinese nation's community" from the perspective of the daily production and life practice of villagers (residents) within the "interembedded community" [12].…”
Section: Introductionmentioning
confidence: 99%
“…The research focuses on the single-ethnic research at the meso-level and the research on colleges and universities [11]. As far as the relevant research results have been found so far, few scholars have discussed the relevant issues of "forging the consciousness of the Chinese nation's community" from the perspective of the daily production and life practice of villagers (residents) within the "interembedded community" [12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the value of the community internal density is important to more understand the evolution of each learners' network [24]. Furthermore, density is one of the most used measures as it reflects the frequency of information flow between learners which acts as an indicator of the network connectedness [56].…”
Section: Experimentation and Resultsmentioning
confidence: 99%
“…However, for other situations, a combined definition seems necessary. In addition, most of the proposed algorithms have considered the network of learners as static, which is not really the case [56]. Much more, the involvement of the dynamicity of the network makes it possible to find more lifelong and stable communities.…”
Section: Community Detection Algorithms For E‐learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Social network analysis has been increasingly applied to the field of education (see review in Yassine et al, 2021). It includes but is not limited to: general engagement analysis for examining the emotional, cognitive, and behavioral interactions between learners and/or resources, behavior assessment which centers on diagnosing learner behaviors to identify any patterns of disorder that may need support and intervention, performance prediction to predict learners' achievement to aid in enhancing the teaching and learning processes, and recommender system development focusing on design filtration systems that provide personalized recommendations to assist learners based on their interest, preferences, and interaction patterns.…”
Section: Social Network Analysismentioning
confidence: 99%